“TO STUDY IRON PROFILE IN CHRONIC LIVER DISEASE IN A TERTIARY CARE HOSPITAL IN MANIPUR.” - Dr. LalmuankimaTlau; Dr. Salam Kenny Singh; Dr. Thangjam Gautam Singh; Dr. Ningthoukhongjam Reema; Dr. Rajkumar Ajaykumar; Dr. Lalhriatpuia chhangte; Dr. Sadziikho Lolee Kriibve; Dr. Sridevi Laishram (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Introduction: Chronic liver disease (CLD) is progressive deterioration of liver functions for more than six months. Chronic liver disease is one of the frequent causes of death, especially in the developing world. The severity of liver disease can be graded by Child Pugh Score. The liver plays a major role in iron homeostasis. Hepatic inflammation and dysfunction in CLD interferes with iron metabolism (including synthesis and clearance). Excess iron deposition in the liver is known to be hepatotoxic and exacerbate liver injury.CLD also decreased synthetic functions of liver including decreased hepcidin level causing ultimately  iron overload and deposits in liver and higher levels of non-transferrin-bound iron in the bloodstream. Iron combined with reactive oxygen species leads to an increase in hydroxyl radicals, which are responsible for phospholipid peroxidation, oxidation of amino acid side chains, DNA strain breaks, and protein fragmentation. Iron deficiency as well as excess of iron, both have harmful effects on the body. Not much studies have been conducted in north-eastern part of India, so we conducted this study to evaluate the iron profile in patients with CLD and its correlation with severity of CLD.Methods: This cross sectional study enrolled 134 chronic liver disease patients above 18 years of age who visited the Medicine outpatient department, Liver clinic  or admitted to the medicine ward, Regional institute of Medical Sciences (RIMS), Imphal from 1st January, 2021 to 31st October 2022. Data were collected randomly using predesigned performa and the severity of liver disease were assessed using Child Pugh Score. Routine haematological and radiological investigations including serum iron, serum ferritin, total iron binding capacity (TIBC), unsaturated iron binding capacity (UIBC) and USG abdomen were done. ANOVA test was performed to test the significance level. A p value < 0.005 was considered significant. Results: A total of 134 patients with chronic liver disease (CLD) were included whose mean age was 48.04 ± 15.67 years with male: female was 4:1. In this study, as per Child Pugh Turcotte Score, majority 67 (50%) of the CLD patients had decompensated liver disease classified as group C, 49 (36.6%) in group B and 13.4% in group A.  The mean serum Iron level was 71.9 with SD of 47.28 mcg/dL with majority 79 (59%) having normal serum Iron levels (50-175 mcg/dL) while 51 (38.1%) of the patients had iron deficiency. Most of the participants 68 (50.7%) had TIBC levels below the normal range of 240 – 450 mcg/dL, maximum patients 82 (61.2%) had UIBC level within the normal range of 111-343 mcg/dL. But, the majority 69 (51.5%) had serum ferritin levels above the normal range of 25-336 mcg/L. Serum Iron level, TIBC, UIBC were highest in child group A and lowest in Child Pugh C which is more severe form of disease while serum ferritin was highest in child group C indicating more rapid increase in the levels of serum ferritin with increase in severity of liver disease. There was no significant association between severity of liver disease and serum iron levels (p value = 0.606) while there were statistically significant associations between serum TIBC,UIBC and serum ferritin with the severity of liver disease (p value